Memoria e imaginación : de la memoria traumática a la imaginación utópica (2017)
ABSTRACT: Over the last century, the problems concerning the manifold relations between memory and imagination have become a major set of studies wherein a wide range of current approaches on social and cultural change are developing. This is the core idea of this section in the twentieth issue of Digithum. The confluence between both socio and temporal notions denotes a fertile realm of contemporary studies within humanities and social sciences. The articles below, each of them in their own way, present the idea that, in order to comprehend the past, its link with the future must be taken into account; otherwise, the two-dimensional character of the socio historical time, as well as the temporal connotation of all that is human, is being neglected.